Effects of clinical interventions through a comprehensive medication management program: A retrospective study among outpatients in a private hospital - Esteban Zavaleta-Monestel; Bruno Serrano-Arias; Sebastián Arguedas-Chacón; Alonso Quirós-Romero; José Pablo Díaz-Madriz; Arturo Villalobos-Madriz; Allan Robles-Calderón; Jorge Bucknor-Masís; José Miguel Chaverri-Fernández (Elsevier, 2024)
Introduction: The intricate nature of certain diseases necessitates complex medication regimens, utilization including high-cost medications, and continual vigilance to avoid potential complications. To address these exigencies, numerous healthcare institutions have instituted multidisciplinary management teams, exemplified in pharmaceutical care through Comprehensive Medication Management (CMM) programs. These programs oversee diverse facets such as patient education, medication adherence promotion, clinical monitoring, dose adjustments, and scrutiny of prescribed drug therapies. Given the emphasized significance, it is relevant to possess evidence to continue endorsing these initiatives from management positions within health centers, and it is for this reason that this study aims to evaluate the clinical and economic benefits provided by a CMM program within a private hospital in Latin America, by analyzing the effects of clinical interventions. Methods: A retrospective examination was conducted involving documented pharmaceutical interventions in an outpatient setting from January 2019 to September 2022. To assess the interventions' repercussions, a retrospective analysis was undertaken. The collated data included patients' basic characteristics, a comprehensive pharmacist-generated description of interventions, potential associated complications, and avoided medical services. Multiple clinical projections, which were endorsed by internal medicine physicians, were developed to explore potential scenarios in the absence of pharmaceutical care. These projections were associated with conceivable complications, aligned with the most plausible circumstances. Subsequently, utilizing the average cost of healthcare within a private hospital in Latin America, the cumulative savings were quantified. These savings were then attributed to the intrinsic advantages offered by pharmaceutical care. Results: The study discloses demographic trends among patients within distinct age groups in the CMM program. Rheumatology predominated as the main referral source, and interventions centering on monitoring emerged as the pivotal drug-related concern. This encompassed a collaborative approach, involving interdisciplinary efforts toward patient education and critical parameter monitoring. Of the total 347 pharmaceutical interventions, 66.3% (N = 230) specialty office visits, 14.1% (N = 49) general practitioner consultations, 12.4% (N = 43) hospitalizations, and 7.2% (N = 25) ER visits were avoided. The economic analysis underscores cost savings ensuing from pharmaceutical interventions, amounting to a cumulative 603,792.82 USD. Extrapolating these findings to a patient cohort of 400 enrolled in the pharmaceutical care program approximates per-patient savings of 361.47 USD. Conclusion: This study reveals the significant clinical and economic benefits of CMM programs, led by multidisciplinary pharmaceutical professionals. The findings provide compelling evidence for hospital management to consider promoting such programs, drawing from the patient-centered care model in the United States applicable to Latin America.